2001
DOI: 10.1126/science.291.5501.118
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Mildew Resistance in Arabidopsis thaliana Mediated by RPW8

Abstract: Plant disease resistance (R) genes control the recognition of specific pathogens and activate subsequent defense responses. We show that the Arabidopsis thaliana locus RESISTANCE TO POWDERY MILDEW8 (RPW8) contains two naturally polymorphic, dominant R genes, RPW8.1 and RPW8.2, which individually control resistance to a broad range of powdery mildew pathogens. Although the predicted RPW8.1 and RPW8.2 proteins are different from the previously characterized R proteins, they induce localized, salicylic acid-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
485
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(499 citation statements)
references
References 22 publications
6
485
3
5
Order By: Relevance
“…To investigate plant–soil feedback at the intraspecific level, we used four natural (not genetically modified) A. thaliana accessions of different origins, namely Col‐0 (origin in Columbia, Missouri, USA), Tsu‐0 (Tsu, Japan), Bur‐0 (Burren, Ireland), and Na‐1 (Nantes, France). As Col‐0 is the most explored accession being used as wild type or reference accession of A. thaliana in most studies (Fahlgren et al., 2006; Frenkel et al., 2009; Xiao et al., 2001), we decided to use this accession in all three parts of the plant–soil feedback experiment.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate plant–soil feedback at the intraspecific level, we used four natural (not genetically modified) A. thaliana accessions of different origins, namely Col‐0 (origin in Columbia, Missouri, USA), Tsu‐0 (Tsu, Japan), Bur‐0 (Burren, Ireland), and Na‐1 (Nantes, France). As Col‐0 is the most explored accession being used as wild type or reference accession of A. thaliana in most studies (Fahlgren et al., 2006; Frenkel et al., 2009; Xiao et al., 2001), we decided to use this accession in all three parts of the plant–soil feedback experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Because most nTNL genes encode a coiled-coil (CC) domain at the N terminus, the nTNL genes often are called CC-NBS-LRR (CNL) genes (Meyers et al, 2003;Ameline-Torregrosa et al, 2008). However, recent studies have revealed that apart from CNL genes, a small group of nTNL genes that possess a special N-terminal domain, RPW8 (resistance to powdery mildew8) domain, likely represent a distinct class of NBS genes (RPW8-NBS-LRR [RNL]; Xiao et al, 2001;Cannon et al, 2004;Bonardi et al, 2011;Collier et al, 2011;Shao et al, 2014;Zhang et al, 2016). Investigations of NBS genes in the Fabaceae (rosid I lineage) and Brassicaceae (rosid II lineage) have shown that RNLs and CNLs diverged prior to the divergence of these two families (Shao et al, 2014;Zhang et al, 2016).…”
mentioning
confidence: 99%
“…RPW8 proteins contain a predicted coiled-coil (CC) and a transmembrane (TM) domain, structurally different from other R proteins identified to date (Table 2). Though RPW8-mediated resistance was previously reported to be effective against O. neolycopersici in the Ms-0 accession, heterologous expression of RPW8 genes in tomato and Arabidopsis failed to confer enhanced resistance to O. neolycopersici (Xiao et al 2001). The RPW8-mediated resistance present in several other Arabidopsis accessions seems to be non-functional against O. neolycopersici.…”
Section: Comparison Of Pm Resistance In Tomato and Arabidopsismentioning
confidence: 83%
“…Known sources of resistance in Arabidopsis comprise natural resistance conferred by alleles of the RPW8 locus and mutation-induced resistance. The RPW8 locus comprises two dominantly inherited R-genes, RPW8.1 and RPW8.2, which control resistance to a broad range of PM species (Xiao et al 2001). RPW8 proteins contain a predicted coiled-coil (CC) and a transmembrane (TM) domain, structurally different from other R proteins identified to date (Table 2).…”
Section: Comparison Of Pm Resistance In Tomato and Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation